2017
DOI: 10.3389/fcimb.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Host Cell Transcription Factor EGR1 Is Induced by Bacteria through the EGFR–ERK1/2 Pathway

Abstract: The essential first step in bacterial colonization is adhesion to the host epithelial cells. The early host-responses post-bacterial adhesions are still poorly understood. Early growth response 1 (EGR1) is an early response transcriptional regulator that can be rapidly induced by various environmental stimuli. Several bacteria can induce EGR1 expression in host cells, but the involved bacterial characteristics and the underlying molecular mechanisms of this response are largely unknown. Here, we show that EGR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017). It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1mentioning
confidence: 99%
See 1 more Smart Citation
“…It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017). It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1mentioning
confidence: 99%
“…EGR1 is a zinc-finger TF that is expressed as an immediate early gene in response to external signals that regulate cell physiology including growth, differentiation, and survival. It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017). Previous reports have shown that EGR1 regulates ATF3 expression in murine αT3-1 cells (Mayer, Dexheimer, Nishida, Kitajima, & Thiel, 2008).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1mentioning
confidence: 99%
“…Teichroeb et al found that NNAT was consistently silenced in iPSCs compared with its isogenic ESCs, and suppression of NNAT could be used as a biomarker for successful reprogramming (17). EGR1 is a zinc-finger pro-differentiation factor that plays an important role in the regulation of differentiation and development in several contexts (19). Recently, Worringer et al suggested that EGR1 might be a barrier to reprogramming of let-7, and inhibition EGR1 mRNA by RNA-binding protein (RBP) LIN-41 could promote reprogramming (18).…”
Section: Validation Of Differently Expressed Genes By Qrt-pcrmentioning
confidence: 99%
“…The integrated phosphoproteomic and transcriptomic analysis in the previous studies showed that PRKD3 may play important roles in a variety of the cancer-related pathways. [17][18][19][20][21][22][23] These ERK1/2-activated downstream factors further regulate many cellular functions, including proliferation, differentiation and transformation. 2,12 However, the interaction mechanisms among PRKD3, ERK1 and c-MYC in cancer cells has not been well-investigated since only one prostate cancer study suggested PRKD3-activated ERK1/2 is involved in tumour growth.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Activated ERK1/2 translocates to the cell nucleus and then phosphorylates a series of transcription factors, such as c-MYC, FOS, FRA1 and EGR1. [17][18][19][20][21][22][23] These ERK1/2-activated downstream factors further regulate many cellular functions, including proliferation, differentiation and transformation. [24][25][26] In mammals, the identity of ERK1 and ERK2 sequences is 84%, but ERK1 has two more amino acids (a.a.) at its C-terminus and 17 more a.a. at N-terminus than ERK2.…”
Section: Introductionmentioning
confidence: 99%